Clinical Phenotype of Endothelial Dysfunction in a Lot of Romanian Scleroderma Patients - Groseanu, Laura (Maedica (Bucur), 2015)
OBJECTIVES: to identify the particularities of the clinical phenotype of endothelial dysfunction in a lot of Romanian patients from a reference center and compare it to data reported by international registries. MATERIALS AND METHODS: 51 patients were included in a cross sectional study. The patients were evaluated for the pattern of disease, main visceral involvement, serum markers of disease. RESULTS: 41.2% patients had history of digital ulcers, 27.45% had pulmonary arterial hypertension; cardiovascular involvement also included: diastolic dysfunction in 31.1% of the patients, global systolic dysfunction in 9.8%, rhythm and conduction disturbances in 19.6%, peripheral vascular disease in 19.6%. Scleroderma renal crisis was identified in 2 patients. CONCLUSION: Vascular complications are a major cause of morbidity and mortality in systemic sclerosis. Earlier therapeutic intervention demands improved screening and diagnosis in all cases.